Binary and ternary metal complexes of Congo red with amino acids - (:unkn) unknown (ELSEVIER SCI LTD, 2006)
The stability constants of the 1:1 binary complexes of Ag+, Ni2+, Co2+, Y3+ metal ions with glutamic acid (Glu), leucine (Leu) and Congo red (CR) and their HA ternary complex and the protonation constants of the ligands were determined potentiometrically at a constant ionic strength of I = 0.10 mol dm(-3) (NaClO4) in aqueous solutions at 15.0, 25.0 and 35 degrees C. The thermodynamic parameters Delta G(o), Delta H-o and Delta S-o were reported for the complex formation reactions. The enthalpy changes of all complexation are found to be negative but entropy changes positive. The driving forces for the formation of Ag-CR, Ni-CR, Co-CR are the enthalpy decreases. But the driving force for Y-CR is the entropy decreases. The driving force of Ni-Glu, Co-Glu, Ni-Leu and Co-Leu systems are about equally enthalpy decrease and entropy increase while Ag-Glu and Ag-Leu complexation are enthalpy stabilized. But, the driving force of Y-Glu and Y-Leu systems are the entropy increase. For formed ternary complexes the reactions are all enthalpy-driven. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Congo red dyes; amino acids; thermodynamic parameters; binary and ternary complexes; metal complexes; Congo red complexes; THERMODYNAMICS; STABILITY; BEHAVIOR; SYSTEMS